2019
DOI: 10.3390/mca24030075
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Multi-Domain Spectral Method for Conjugate Problems of Conduction and MHD Free Convection Flow of Nanofluids over Flat Plates

Abstract: An efficient overlapping multi-domain spectral method is used in the analysis of conjugate problems of heat conduction in solid walls coupled with laminar magnetohydrodynamic (MHD) free convective boundary layer flow of copper (Cu) water and silver (Ag) water nanofluids over vertical and horizontal flat plates. The combined effects of heat generation and thermal radiation on the flow has been analyzed by imposing a magnetic field along the direction of the flow to control the motion of electrically conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…where α is the overlapping distance between two intervals. We note that 8) which upon rearranging and making Lx the subject of the formula gives Eq. (23).…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…where α is the overlapping distance between two intervals. We note that 8) which upon rearranging and making Lx the subject of the formula gives Eq. (23).…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…In the non-overlapping multi-domain BSQLM, the multi-domain technique was only applied in time. Recently, Mkhatshwa et al [8,9] found that the accuracy of the BSQLM can be improved by applying the overlapping multi-domain technique in the space interval and the non-overlapping multi-domain technique in the time interval. Teleei and Dehghan [10] introduced a numerical scheme for the solution of sine-Gordon equation when only space discretization is performed by an overlapping multi-domain pseudo-spectral technique.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49] In all these studies, the overlapping multidomain approach was applied only in the spatial domain, and it was found that the accuracy of pseudospectral methods improved through the use of overlapping grid procedure. Mkhatshwa et al 48 and Mkhatshwa et al 49 considered nonlinear PDEs modeling problems that arise in fluid mechanics. The BSQLM on overlapping grids was introduced by Mkhatshwa et al 38 and implemented to solve time-dependent Emden-Fowler equations.…”
Section: Introductionmentioning
confidence: 99%
“…The single‐domain BSQLM method uses quasilinearization technique, 45 the Chebyshev spectral collocation method, as well as the bivariate Lagrange interpolation polynomial with Chebyshev‐Gauss‐Lobatto grid points. The overlapping multidomain technique with pseudospectral methods has been considered by several researchers 46‐49 . In all these studies, the overlapping multidomain approach was applied only in the spatial domain, and it was found that the accuracy of pseudospectral methods improved through the use of overlapping grid procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer with convective boundary conditions is implicated in mechanisms like gas turbines, thermal energy storage, nuclear power plants etc.. In this context, some recent studies [26][27][28][29][30][31] are observed in which the study of non-Newtonian fluid flows with peristalsis are conducted in the vicinity of convective conditions.…”
Section: Introductionmentioning
confidence: 99%